EXPERIMENTAL AND THEORETICAL CONSTRAINTS ON MELT DISTRIBUTION IN CRUSTAL SOURCES: THE EFFECT OF CRYSTALLINE ANISOTROPY ON MELT INTERCONNECTIVITY - Laporte D.; Watson E.B. (My University, 1995)
In partially molten systems, the equilibrium distribution of melt at the grain scale is governed by the principle of interfacial energy minimization. In ideal sources (i.e. partially molten rocks that are monomineralic, have single-valued solid-liquid and solid-solid interfacial energies, and are subject to hydrostatic stress) the wetting angle Θ is known to be a unique characteristic which specifies the melt configuration for a given melt fraction. Crustal rocks cannot be modelled as ideal sources because of their polymineralic nature, the moderate to high anisotropy of interfacial energies which characterizes common refractory minerals, and the possible presence of a crystallographic preferred orientation. That partially molten crustal rocks depart from ideal sources is documented by a series of high-P, high-T experiments illustrating the textural relationships of biotite and amphibole with silicic melts. The melt distributions observed in these experiments differ significantly from those expected in ideal sources: (1) crystal-melt interfaces are commonly planar, rational faces rather than smoothly curved, irrational surfaces; and (2) the concept of a unique wetting angle does not hold as shown in the biotite-silicic melt system. These textural features demonstrate that anisotropy of crystal-melt interfacial energy is a factor of primary importance in modelling the grain-scale distribution of partial melts. The petrological implications of our study are the following: (1) At high degrees of anisotropy and low melt fractions, melt is predicted to form isolated, plane-faced pockets at grain corners. The overall shape of these pockets, and therefore the value of the connectivity threshold oc, are expected to be very sensitive to the ratio of solid-solid to solid-liquid interfacial energies, γsssl (oc is the melt fraction at which melt interconnectivity is established). Melt pockets with low volume-to-surface ratio, and low (but non-constant) wetting angles should prevail at high γsssl, resulting in very low values of oc (=< 1 to a few vol%). Higher values of oc, a high volume-to-surface ratio of melt pockets, and high wetting angles are expected at low γsssl.(2) The wetting angle at hornblende-hornblende-melt junctions, at 1200 MPa-975°C, is 25°. A review of existing data indicates that quartz-melt and feldspar-melt wetting angles are also low to moderate (12-60°). A very low value of oc should, therefore, be the general rule during crustal anatexis. In particular, a connectivity threshold lower than 3-4 vol% is predicted for partially molten amphibolite.(3) In biotite-rich rock-types, such as melanosomes in migmatites, the combination of a pronounced crystalline anisotropy and a marked preferred orientation of mica flakes leads to a very low permeability (normal to layering). Biotite-rich melanosomes should therefore impede chemical interactions between neighbouring leucosomes and mesosomes.